Assessing Domain Specificity in the Measurement of Mathematics Calculation Anxiety. (3rd February 2019) - Hunt, Thomas E.; Bagdasar, Ovidiu; Sheffield, David; Schofield, Malcolm B.
Abstract : An online, cross-sectional approach was taken, including an opportunity sample of 160 undergraduate students from a university in the Midlands, UK. Exploratory factor analysis indicated a parsimonious, four-factor solution: abstract maths anxiety, statistics probability anxiety, statistics calculation anxiety, and numerical calculation anxiety . The results support previous evidence for the existence of a separate "numerical anxiety" or "arithmetic computation" anxiety component of maths anxiety and also support the existence of anxiety that is specific to more abstract maths. This is the first study to consider the multidimensionality of maths anxiety at the level of the calculation type. The 26-item Maths Calculation Anxiety Scale appears to be a useful measurement tool in the context of maths calculation specifically.